Faktor-Faktor yang Mempengaruhi Keputusan Orang Tua Siswa Memilih SD Kasatriyan Surakarta - Nuning Kristiani (Universitas Kristen Maranatha, 2016)
The Kasatriyan elementary school (SD Kasatriyan) is one of the oldest elementary schools in Surakarta and was founded on November 1, 1901 by Sinuhun Pakubowono X. Located in the neighborhood of Surakarta Palace, in the beginningonly accepts male students from the members of the royal family. However, in 1983 developed to accept female students and the general students from outside the royalfamily members. In the 2000s, the Kasatriyan elementary school has decreased the number of students. This problem may have happened because the establishment ofnew schools which have advantages in terms of facilities, curriculum development and the hiring of foreign teachers. The elementary school is the business of educational services that using the marketing mix to introduce the services offered.Therefore, in this research used the marketing mix to determine the factors that influence the decision to choose SD Kasatriyan. This study used a sample of 50respondents from the parents of elementary school students Kasatriyan. The results showed that variables such as promotions, services, and accreditation status has aninfluence on the decision of parents to choose the SD Kasatriyan. Meanwhile, other variables such as product, cost, and location, are not shown to affect the decision of parents to choose the SD Kasatriyan.